Rheumatoid factors from the peripheral blood of two patients with rheumatoid arthritis are genetically heterogeneous and somatically mutated. - Youngblood, K; Fruchter, L; Ding, G; Lopez, J; Bonagura, V; Davidson, A (The Journal of Clinical Investigation, 1994)
We report the DNA sequences of the heavy and light chain immunoglobulin genes of 11 monoclonal rheumatoid factor (RF)-secreting lines derived from the peripheral blood of two patients with rheumatoid arthritis (RA). It is evident from immunogenetic analysis of these lines that RA-associated RF activity can arise from a wide variety of heavy and light chain genes and gene combinations. Although the RF response from our two patients shows a bias in gene usage toward those genes used to encode monoclonal RF, particularly VkIII, relatively few of these RFs are reactive with the monoclonal antiidiotypes 6B6.6 and 17.109 that define VkIII germline-encoded light chains and the loss of this idiotypic reactivity is clearly related to somatic mutation. Finally, RFs derived from peripheral blood of RA patients show a similar heterogeneity of epitope binding to Fc as that seen for synovium-derived RF and some are clearly different in binding specificity from the restricted RF population found in patients with B cell malignancies. Somatic mutations as well as different VH/VL combinations contribute to the heterogeneity in the binding patterns of these RA-derived RF. Images